Creative Cities in the EU Outermost Regions: From Cultural Entrepreneurship to Cultural Policies | Cidades Criativas nas Regiões Periféricas da UE: Do Empreendedorismo Cultural às Políticas Culturais - Patricia Oliveira (Political Observer, 2024)
This article seeks to explore two main conceptual dimensions — cultural policies and cultural entrepreneurship — as well as its impacts in the framework of creative cities in the European Union Outermost Regions (ORs). Through a comprehensive analysis, in this article are considered general trends and goals for the cultural world settled in different institutional levels of political discourse, such as the strategic partnership between UNESCO and the European Union. Tackling the post-pandemic political agenda facing global challenges, this article seeks to explore in what extend cultural entrepreneurship enhances governance systems for cultural and creative industries focused on resilience and sustainability.